2014
DOI: 10.1074/jbc.m113.537258
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Scavenger Receptor BI Protects Against Polymicrobial-induced Sepsis through Promoting LPS Clearance in Mice

Abstract: Background: We utilized Scarb1I179N mice, a model deficient in hepatic SR-BI, to determine the role of hepatic SR-BI in sepsis. Results: Upon cecal ligation and puncture (CLP), Scarb1 I179N mice had a 3.5-fold increase in fatality associated with an impaired LPS clearance. Conclusion: Hepatic SR-BI protects against sepsis through promoting LPS clearance. Significance: Promoting hepatic SR-BI-mediated LPS clearance may provide a therapeutic approach for sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 76 publications
2
33
0
2
Order By: Relevance
“…As expected, lipopolysaccharide resulted in a significant increase in tissue uptake for all tissues and organs studied, with liver showing the largest uptake overall across time points. These data are consistent with prior reports implicating liver as a primary route of lipopolysaccharide clearance during bacterial sepsis (27,28). Moreover, hepatic myeloid interstitial dendritic cell ectonucleoside triphosphate diphosphohydrolase-1 (CD39) hyporesponsiveness has been reported in mice (29).…”
Section: Discussionsupporting
confidence: 82%
“…As expected, lipopolysaccharide resulted in a significant increase in tissue uptake for all tissues and organs studied, with liver showing the largest uptake overall across time points. These data are consistent with prior reports implicating liver as a primary route of lipopolysaccharide clearance during bacterial sepsis (27,28). Moreover, hepatic myeloid interstitial dendritic cell ectonucleoside triphosphate diphosphohydrolase-1 (CD39) hyporesponsiveness has been reported in mice (29).…”
Section: Discussionsupporting
confidence: 82%
“…Recent studies in our laboratory and others demonstrated that SR-BI is a critical protective factor in sepsis (24)(25)(26)(27)(28)(29)(30)(31). SR-BI is most abundantly expressed in adrenal glands, mediating intracellular cholesterol uptake from HDL for corticosteroid synthesis (22,32).…”
mentioning
confidence: 98%
“…A third mechanism of SR-B1 to promote tumor growth is by the inhibition of acute inflammation [73,74]. SR-B1 has been implicated in several biological processes such as apoptosis [86,87], sepsis [88], binding and internalization of endogenous proteins and pathogens and, in most cases, its signaling pathway is associated with an anti-inflammatory response [73,74]. In the steady state, HDL interaction with SR-B1 inhibits the expression of adhesion molecules on endothelial cells activating the nitric oxide synthase [87].…”
Section: Sr-b1 Promotes Cancer Progression: Sr-b1 Antagonist As Anti-mentioning
confidence: 99%
“…Moreover, microbial by-products are removed via SR-B1. For instance, SR-B1 can bind and internalize LPS without triggering an inflammatory signaling cascade, thus limiting the bioavailability of LPS and dampening the inflammatory response triggered via TLR4 [88]. A similar situation applies to the role of SR-B1 in modulating the response of B cells to CpG oligonucleotides; CpG binding to SR-B1 on the B-cell surface was shown to trigger Ca 2+ entry through TRPC3 channels, leading to dampened cytokine production in response to CpG via TLR9 activation [90].…”
Section: Sr-b1 Promotes Cancer Progression: Sr-b1 Antagonist As Anti-mentioning
confidence: 99%